STRUKTUR KOMUNITAS ZONA RIPARIAN TERHADAP KONDISI FISIK-KIMIA KELOMPOK HUTAN SUNGAI KUBANG PT. ERNA DJULIAWATI - Erianto, Erianto; Marissa, Dila; Dewantara, Iswan (Universitas Tanjungpura, 2025)
PT. Erna Djuliawati Central Kalimantan is a company engaged in the timber industry, in the PBPH area there are many Sub-Watersheds, one of which is the Kubang Sub-DAS This study aims to identify the community structure of riparian vegetation in the waters of the Kubang River and analyze the quality and conditions of the physical and chemical waters of the Kubang River. This study uses a survey method with a purposive sampling technique. The results of the study showed that there were 43 species of riparian vegetation at the lower plant level with 149 individuals, 18 species of seedlings with 94 individuals, 31 species of stakes with 125 individuals, 20 species of poles with 110 individuals, and 30 species of trees with 173 individuals. Riparian diversity between tilapia H 0.82-1.27 is in the low to medium category. The distribution pattern of vegetation at each station shows that all vegetation growth stages are distributed in a clustered pattern, except for the seedling stage at the downstream section of the river, which is distributed randomly.. Based on the results of the Kubang River water quality laboratory test, the values of BOD 1-2, COD 3.0-13, DO 4.05-4.47, pH 7.12-7.78, TSS 5.0-10, and TDS 24-25 are included in the standard water quality. Keywords: Distribution patterns, diversity, physico-chemical, riparian vegetation. Abstrak PT. Erna Djuliawati Kalimantan Tengah merupakan perusahaan yang bergerak dibidang industri kayu, dalam kawasan PBPH terdapat banyak Sub Daerah Aliran Sungai salah satunya Sub DAS Kubang. Penelitian ini bertujuan untuk mengindentifikasi struktur komunitas vegetasi riparian di kawasan perairan Sungai Kubang dan menganalisis kualitas dan kondisi perairan fisik kimia Sungai Kubang. Penelitian ini menggunakan metode survey dengan teknik purposive sampling. Hasil penelitian menunjukan bahwa vegetasi riparian tingkat tumbuhan bawah ditemukan 43 jenis dengan 149 individu, 18 jenis semai dengan 94 individu, 31 jenis pancang dengan 125 individu, 20 jenis tiang dengan 110 individu, 30 jenis pohon dengan 173 individu. Keanekaragaman jenis vegetasi riparian adalah H 0,82-1,27 termasuk ke dalam kategori rendah sampai sedang. Pola penyebaran vegetasi pada setiap stasiun menunjukan semua tingkat pertumbuhan vegetasi tersebar secara berkelompok dan hanya tingkat pertumbuhan semai pada sungai bagian hilir tersebar secara acak. Berdasarkan hasil uji laboratorium kualitas air Sungai Kubang nilai BOD 1-2, COD 3,0-13, DO 4,05-4,47, pH 7,12-7,78, TSS 5,0-10, TDS 24-25 masuk kedalam standar baku mutu air. Kata kunci: Pola distribusi, keanekaragaman, fisik-kimia, vegetasi riparian.